A Study of Dynamic Effects on the Human Body in External Physical Shock - Choi, Min Ki (한양대학교, 2019)
현재 개인 병사의 생존성과 임무수행능력에 대한 중요성은 꾸준히 부각되고 있으며 미래의 전장에 대처할 수 있는 하박 장착용 스마트 개인화기 무기체계에 대한 연구개발이 필요한 실정이다. 이로 인해 하박 장착용 스마트 개인화기가 인체에 미치는 영향을 예측할 필요가 있다. 그래서 본 연구는 인체와 총기 결합 모델의 초기 연구로 1 가지의 충격량에 대하여 2 가지의 자세 형태를 분석하여 외부의 물리적 충격에 의한 인체거동 해석을 연구 목적으로 하고 있다. 본 연구는 LifeMOD & ADAMS 소프트웨어를 사용하여 Passive Simulation과 Active Simulation을 수행하였다. Passive Simulation 기능을 사용하여 가상에서 발생할 수 있는 외부의 물리적 충격에 의한 인체 거동을 해석하였다. 또한 Active Simulation 기능을 사용하여 실제로 외부의 물리적 충격에 대해 인체가 어떠한 거동을 보이는지 해석하였다. 실제의 실험에서는 아직 개발 되지 않은 하박 장착용 스마트 개인화기를 대체할 간단한 실험 장비(진자 이용)를 제작하여 실험하였다. 그 다음 같은 조건 상황에서 Passive Simulation의 인체 거동 데이터와 Active Simulation의 인체 거동 데이터가 정량적으로 어느 정도의 차이를 보이는지 파악하기 위해 몇 가지 관절의 변위 수치를 파악하고 비교하였다. 이를 통하여 미래의 하박 장착용 스마트 개인화기의 인체 적합성을 분석하였다.; Currently, the importance of individual soldier’s survivability and mission performance is steadily rising, and it is necessary to research and develop smart personal firearms system launched at forearm to cope with future battlefields. Therefore, it is necessary to predict the effect of smart personal firearms launched at forearm on human body. Therefore, this study is the initial study of coupling model of human body and firearm launched at forearm, and this study is aimed to study the human body behavior by external physical shock by analyzing two types of posture for one impulse. In this study, passive simulation and active simulation were performed using LifeMOD & ADAMS software. Passive simulation function is used to analyze the human body behavior due to external physical shock that may occur in the virtual environment. In addition, using the active simulation function, the behavior of the human body against the actual physical shock was analyzed. In the actual experiment, simple experimental device (using pendulum) to replace the smart personal firearms launched at forearm which has not yet been developed has been manufactured and experimented. In order to apprehend how the human behavior data of passive simulation and the human behavior data of active simulation are quantitatively different from each other under the same condition, the displacement values ​​of several joints were grasped and compared. Through this process, the human body suitability of the smart personal firearms launched at forearm of future was analyzed.